Cornsilk as an Alternate Functional Ingredient - Ishak, Wan Rosli Wan; Rahman, Nurhanan Abdul (Penerbit Universiti Putra Malaysia, 2017)
Corn trees have been cultivated about 5000 years ago and it is known to be derived from a wild grass native to Mexico and Central America (Dermastia et al., 2009). The name ‘Zea’ comes from the Greek word which means cereal or grain and the word ‘mays’ is adopted from a Spanish voyager named Columbus, who collected the grain and brought it over to Europe from America (Desjardins & McCarthy, 2004; Eckhoff et al., 2009). Since its domestication, corn plant spreads rapidly around the world in the 15th century, mainly in the temperate regions (Eckoff et al., 2009). Corn is introduced into Mediterranean and South East Asia region in the 16th century by the Portuguese (Desjardin & McCarty, 2004). Corn tree is about 5 to 7 feet tall having long and green leaves attached to its stalk. It requires a warm weather climate, nutrient rich soil and abundant moisture for growth. Corn plant is monoecious which means both male and female flowers develop on the same plant. Its male flower or sometimes referred to as tassel is located on top of the plant while the female flower developed from shoots and arises from between the stalk and leaf sheath. Female inflorescence also refers as an ‘ear’. Normally, two to three shoots are found within one stalk of the corn plant. Male inflorescences are seen on top of a corn plant and are actively involved in pollination.